PENGARUH KEPEMIMPINAN SITUASIONAL DAN PEMBERIAN MOTIVASI KEPALA SEKOLAH TERHADAP KINERJA GURU SD - Agus Arizal; Aswandi Aswandi; Masluyah Suib (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThis research hopes to reveal the influence of the principal's situational leadership and the principal's motivation giving to the performance of elementary school teachers in Sebawi Sub-district, Sambas District. The research method is descriptive and the data collection technique is done by using a questionnaire. The sample of this research is elementary teacher in Sebawi sub-district of Sambas regency that is 57 respondents. The instrument consists of three variables that are principal situational leadership (X1), principal motivation (X2), and teacher performance (Y).Based on the analysis, this research obtained some findings. First, there was a significant influence between the principal's situational leadership on the performance of elementary school teachers, secondly, there was a significant influence between the principal's motivation giving toward the performance of elementary school, and thirdly, there was a significant influence between situational leadership and principal's motivation giving toward teacher performance.On the basis of the results of the study, for a principal to improve the teachers' performance, he needs to apply situational leadership style and should be able to provide motivation to improve the teachers' enthusiasm and performance. Meanwhile, the teachers are advised to always improve their performance for the sake of the improvement of the quality of education.Keywords: Headmaster's principal leadership, principal motivation, teacher performance